Analisis Kepuasan Nasabah Pasca Pemulihan Pelayanan Pada Pt. Bank Sinar Harapan Bali Pusat - Ariyawan, Agus Hendra Yoga; Pramudana, Komang Agus Satria (E-Jurnal Manajemen; Vol 3 No 12 (2014), 2014)
Every company engaged in the field of banking services at certain times will experience a service failure that could negatively impact the image and reputation of the company and also have an impact on customer satisfaction. Service recovery can generally be applied in three ways: interactional justice, distributive justice, and procedural justice. This research was conducted at PT. Central Bank Sinar Harapan Bali. The number of samples taken were 112 respondents, with purposive sampling method. Data collected through the questionnaire and literature review. The alysis techniqueiused is multipleilinear regression. Basedmon themanalysis it was foundothat, interactional justice, distributive justice, procedural justice and positiveiandisignificant impact on customerisatisfaction at PT. Central Bank Sinar Harapan Bali. The PT. Bank Sinar Harapan Bali Center should continue to improve its services to evaluate existing services to be able to retain customers and strengthen the company's image.
Keywords: pemulihan pelayanan, keadilan interaksional, keadilan distributif, keadilan prosedural, kepuasan nasabah